2004
DOI: 10.1177/147323000403200109
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6-Induced Reciprocal Expression of SERCA and Natriuretic Peptides mRNA in Cultured Rat Ventricular Myocytes

Abstract: We investigated the effect of interleukin-6 (IL-6) expression on sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA), atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) mRNA levels in cultured rat neonatal ventricular myocytes. IL-6 plays a key role in regulating cardiac hypertrophy and the development of heart failure, and SERCA, ANP and BNP are all cardiac hormones with regulatory properties. Compared with baseline measurements, treatment with 50 U/ml IL-6 significantly decreased SERCA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 17 publications
3
41
0
4
Order By: Relevance
“…Increased IL-6 might induce the fetal gene expression pattern observed in Fig. 5A, as previous studies reported such evidence in cultured cardiac myocytes (44,45).…”
Section: Discussionsupporting
confidence: 57%
“…Increased IL-6 might induce the fetal gene expression pattern observed in Fig. 5A, as previous studies reported such evidence in cultured cardiac myocytes (44,45).…”
Section: Discussionsupporting
confidence: 57%
“…Whilst we think that events occuring in the first days of life happen to be much more complex representing "early transition" and should be discussed separately, we believe this data pointing to increased NT-ProBNP levels in infants with TTN with normal cardiac functions is of value. Moreover, few studies provided evidence that the secretion of natriuretic peptides is induced by cytokines and inflammatory mediators (24,25). This information might be regarded as an additional factor resulting in increased plasma peptide levels in LRTI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in these infants, due to prematurity, we observed the high release of FiO2 and BARO/VALU TROMA factors followed by the release of inflamed cytokines and chomocyns which determinate damage of the epithelial and endothelial cells and comsequently the decrease in the synthesis of surfactant and the production of RDS. As cytokines play a role in BNP monitoring (28), in prematurity, their increase elevates the BNP level which shows RDS frequency. In the present study, reduction of birth age was associated with the increment of serum BNP level.…”
Section: Discussionmentioning
confidence: 99%